2016
DOI: 10.1007/s00394-016-1222-0
|View full text |Cite
|
Sign up to set email alerts
|

The pro-/anti-inflammatory effects of different fatty acids on visceral adipocytes are partially mediated by GPR120

Abstract: FAs are capable of directly acting on visceral adipocytes to modulate differently TNF-α, IL-6, IL-10 and adiponectin expression, with a different and greater effect in MO subjects. These effects are largely annulled when GPR120 expression was silenced, which suggests that they could be mediated by GPR120.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
0
29
1
Order By: Relevance
“…There is also evidence suggesting that SFAs may increase the ER stress which, in turn, induces the expression of inflammatory genes and ER chaperones including GRP78 (Figure 1). Besides the mechanistic pathways described above, SFAs may also induce inflammation via binding to Gprotein-coupled receptors (GPRs) 23 or production of ceramides. 29,134,135 The increased production of ceramides may contribute to the activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence suggesting that SFAs may increase the ER stress which, in turn, induces the expression of inflammatory genes and ER chaperones including GRP78 (Figure 1). Besides the mechanistic pathways described above, SFAs may also induce inflammation via binding to Gprotein-coupled receptors (GPRs) 23 or production of ceramides. 29,134,135 The increased production of ceramides may contribute to the activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…35 Both stearic acid and palmitic acid induce the activation of NF-κB and stimulate the secretion of pro-inflammatory mediators in trophoblast cells isolated from human placentas, 36,37 microglial cells, 38 and prostate epithelial cells. 39 Similarly, palmitic acid significantly activates JNK in HEPG2 cells; 40 increases the expression of MCP-1 in mesangial cells; 15 induces the expression of IL-6, IL-8, and MCP-1 in smooth muscle cells; 41,42 increases the activation of p38, JNK, and NF-κB with enhanced expression of TNFα in C2C12 skeletal muscle cells; 43,44 enhances the activation of NF-κB with increased production of IL-6 and TNF-α in adipocytes; 23,45 and induces the activation of p38, ERK, and JNK with increased expression of COX-2, IL-6 and MCP-1 in fibroblast cells. 46,47 Dietary supplementation with high-fat diet (HFD) or infusion of Liposyn II (a 20% triglyceride nonpyrogenic emulsion), lipid/heparin, soybean oil, lard oil, or fatty acids has been used to increase circulating FFA level in human and animal model studies.…”
Section: Long-chain Sfas Increase the Production Of Inflammatory Medimentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to canola oil, the amount of oleic and palmitoleic acid in olive oil is higher. In vitro studies have shown that the addition of oleic or palmitoleic acid to the cell culture medium is effective in reducing or preventing increases in IL-6 levels [23][24][25][26]. Some human studies have shown evidence of an inverse association between oleic acid and IL-6 concentration [27].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to canola oil, the amount of oleic and palmitoleic acid in olive oil is higher. In vitro studies have shown that the addition of oleic or palmitoleic acid to the cell culture medium is effective in reducing or preventing the increase of IL-6 levels [20][21][22][23]. Some human studies have also shown evidence of an inverse association between oleic acid and IL-6 concentration [24].…”
Section: Discussionmentioning
confidence: 99%